Comparing selected higher education systems in Asia - Kaur, Sarjit; Abdul Rahman, Shukran; Koo, Yew Liw; Mohammad Lotfie, Maskanah; Zakariya, Hafiz (Institut Terjemahan dan Buku Negara and IPPTN, 2014)
This book reports a comparison of a selected higher education systems or selected countries in the Asia Pacific.